Legal Protection for Victims of the Crime of Exploitation of Street Minors - Hafidati, Putri (International Journal of Business, Law, and Education, 2025)
Children are invaluable assets of the nation and holders of fundamental human rights; however, they remain highly vulnerable to economic and sexual exploitation. Various exploitative practices, including deceptive job offers promising financial benefits, frequently trap street children in harmful conditions. This study examines the forms of legal protection available to victims, the underlying factors contributing to crimes of child exploitation, and the efforts of law enforcement authorities in addressing these offenses, along with the obstacles they face. The research employs a normative–empirical legal approach by analyzing relevant legislation and its implementation in societal legal practices. The findings indicate that legal action against child exploitation primarily refers to Law No. 35 of 2014, while prioritizing the protection of children’s rights to prevent further victimization. Law enforcement measures include investigation, arrest, prosecution, victim protection, and preventive actions supported by public participation. Nevertheless, limited reporting, delayed disclosure by victims, and low public awareness hinder effective protection and handling of exploitation cases.